ACEing the person-centred choice of anti-obesity therapy - Nishant Raizada; Sanjay Kalra; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
The "3 ACE Check List" is an innovative framework that aims to guide clinicians in selecting appropriate anti-obesity therapy. The 3ACE list consists of nine factors, attractively, alliteratively and accurately listed in three columns. These facets represent the entire biopsychosocio- environmental spectrum of determinants of obesity. It simplifies decisionmaking, by helping clinicians match therapeutic choices with individual patient characteristics, so as to optimize outcomes and satisfaction. We suggest the use of this model in obesity counselling and care. Keywords: Biopsychosocial, counselling, obesity, overweight, person centred care